Leber Congenital Amaurosis Due to GUCY2D Mutations: Longitudinal Analysis of Retinal Structure and Visual Function - Jacobson, Samuel G. (Int J Mol Sci, 2021)
Gene augmentation therapy is being planned for GUCY2D-associated Leber congenital amaurosis (LCA). To increase our understanding of the natural history of GUCY2D-LCA, patients were evaluated twice with an interval of 4 to 7 years between visits using safety and efficacy outcome measures previously determined to be useful for monitoring this disorder. In this group of molecularly-identified LCA patients (n = 10; ages 7–37 years at first visit), optical coherence tomography (OCT) was used to measure foveal cone outer nuclear layer (ONL) thickness and rod ONL at a superior retinal locus. Full-field stimulus testing (FST) with chromatic stimuli in dark- and light-adapted states was used to assay rod and cone vision. Changes in OCT and FST over the interval were mostly attributable to inter-visit variability. There were no major negative changes in structure or function across the cohort and over the intervals studied. Variation in severity of disease expression between patients occurs; however, despite difficulties in quantifying structure and function in such seriously visually impaired individuals with nystagmus, the present work supports the use of OCT as a safety outcome and FST as an efficacy outcome in a clinical trial of GUCY2D-LCA. A wide age spectrum for therapy was confirmed, and there was relative stability of structure and function during a typical time interval for clinical trials.